Nurses in Iraq Show Alarmingly Low Infection Control Adherence: Perawat di Irak Tunjukkan Kepatuhan Pengendalian Infeksi yang Mengkhawatirkan - Alyaa H. Ali (Academia Open, 2024)
This study assesses nurses' adherence to standard precautions and infection management at the Republican Hospital in Basrah through a descriptive cross-sectional survey of 50 nurses, using a WHO-guideline-based questionnaire. The results indicate poor practice among 86% of nurses, with significant differences in adherence across age groups and workplace settings. The findings highlight the necessity for regular, targeted education to improve infection control practices, thus enhancing patient safety and care quality. Highlights: High Non-Adherence: 86% of nurses show poor infection control practices. Demographic Differences: Age, workplace impact standard precaution adherence. Need for Education: Targeted training essential to enhance safety. Keywords: Nurses’ Commitment, Health Guidelines, Infection Control, Standard Precautions, Healthcare Safety